Serum ferritin and injuries in female high school cross country runners - Loosli, A. R.; Requa, R. K.; Garrick, J. G. (Medicine & Science in Sports & Exercise, 1993)
Female runners (N = 101) were assessed for Hgb, serum ferritin levels, and time-loss injuries. Hgb averaged 13.4 gm/ml (range 11.6 - 15.2). Serum ferritin ranged from 7 ng/ml to 62 ng/ml with an average of 20.5 ng/ml. There was no relationship between Hgb and injuries. The average ferritin levels in the no-injury group was 36 - 40% higher than the injury group. The third with the lowest ferritin values had twice as many time-loss overuse injuries as the runners with the highest values. Implication: It is suggested that low total-body iron is related to sports injuries in some populations and its role in sports injuries should be examined further.